2015
DOI: 10.3109/02813432.2015.1084766
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical impact of potentially inappropriate medications during hospitalization of acutely ill older patients with multimorbidity

Abstract: Objective: To identify potentially inappropriate medications (PIMs), to compare drug changes between geriatric and other medical wards, and to investigate the clinical impact of PIMs in acutely hospitalized older adults.Setting and subjects: Retrospective study of 232 home-dwelling, multimorbid older adults (aged ≥75 years) acutely admitted to Vestfold Hospital Trust, Norway.Main outcome measures. PIMs were identified by Norwegian general practice (NORGEP) criteria and Beers’ 2012 criteria. Clinical correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 29 publications
(33 reference statements)
3
68
0
2
Order By: Relevance
“…Transitions of care, especially hospitalizations, common in the course of dementia play a key role in medication management. They offer an opportunity for medication review and deprescription but may also lead to an increased use of medications . During hospitalization, medications may be added to treat health problems that led to admission or conditions that occurred or worsened during hospitalization (such as agitation, pain, delirium, or infections) and may be maintained after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Transitions of care, especially hospitalizations, common in the course of dementia play a key role in medication management. They offer an opportunity for medication review and deprescription but may also lead to an increased use of medications . During hospitalization, medications may be added to treat health problems that led to admission or conditions that occurred or worsened during hospitalization (such as agitation, pain, delirium, or infections) and may be maintained after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Certain changes in drug prescription profiles were found before and after hospitalization, such as an increase in the proportion of patients using antithrombotic agents and lipid modifying agents due to the high prevalence of cardiovascular diseases. A reduction in the number of patients who were prescribed psycholeptics, mainly diazepam, was highlighted, as reported by the Norwegian study (Kersten et al, 2015). A prospective cohort study with patients aged 70 years and over in Australian hospitals investigated the use of benzodiazepines in acute care settings and explored the association with falls before (during a 90-day period prior to admission) and during hospitalization.…”
Section: Discussionmentioning
confidence: 88%
“…The study used the Norwegian General Practice (NORGEP) criteria for PIM. The authors also found that the medication profile was more appropriate among elderly patients in the geriatric ward and a greater reduction of dosage and prescription of PIMs in comparison to other patients (Kersten et al, 2015). Certain changes in drug prescription profiles were found before and after hospitalization, such as an increase in the proportion of patients using antithrombotic agents and lipid modifying agents due to the high prevalence of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Regueiro et al (17) , evaluaron el uso de medicamentos y la prescripción inadecuada en 215 adultos mayores de la comunidad en ciudad de La Plata, encontrando frecuencias de medicación potencialmente inapropiada en 25,5%, 31,9% y 30% según los criterios de Beers, lista PRISCUS y criterios STOPP. Kersten et al (18) también evaluaron a 232 adultos mayores de 75 años, procedentes de la comunidad y con comorbilidad, admitidos a emergencia, encontrando que la hospitalización no cambió la frecuencia de polifarmacia o el uso de medicación potencialmente inapropiada, hubo mejor manejo de medicación por equipos geriátricos multidisciplinario y no hubo impacto en las mediciones clínicas evaluadas (mental, funcional, fragilidad y velocidad de la marcha).…”
Section: La Prescripción Inadecuada De Medicamentos En El Adulto Mayorunclassified